Application of Nanosystems Synergized by Optics and Chemotherapy in the Treatment of Sports Rehabilitation Diseases - Zhiwei Peng; Xianxiong Li; Yu Zhang (Journal of Chemistry)
With the rapid development of sports in my country, many athletes will have mild or severe diseases. Physical rehabilitation can improve their physical pain, and some more serious diseases require optical and chemotherapy treatments. This article mainly studies the application of nanosystems that cooperate with optical and chemotherapy in the treatment of sports rehabilitation diseases. In the experiment, the bacteria-infected mice in the wound were divided into 5 groups (n = 4), and the mouse wound model was made. After that, the number of bacteria remaining in the wound was determined by the plate count method. At the same time, a cytotoxicity test was performed, and a control experiment was performed on the cell culture of the polymer at a concentration below the VCR and CMC values. The final sections were used for tissue analysis of serine and epoxy staining. It was found from the experimental data that the cumulative release of free CLB molecules within 3 hours almost reached 100%, and its rapid release was attributed to its small molecular size. In contrast, the release of CLB-HDH micelles in 3 h is 62%, which has a certain relaxation effect. The results showed that CLB-HDH micelles significantly inhibited tumor growth, had good safety in vivo, and had low systemic toxicity. CLB-HDH micelles provide new ideas for efficient CLB tumor treatment.